Pediatric emergency department visits and ambient Air pollution in the U.S. State of Georgia: a case-crossover study - Xiao, Qingyang (Environ Health, 2016)
BACKGROUND: Estimating the health effects of ambient air pollutant mixtures is necessary to understand the risk of real-life air pollution exposures. METHODS: Pediatric Emergency Department (ED) visit records for asthma or wheeze (n = 148,256), bronchitis (n = 84,597), pneumonia (n = 90,063), otitis media (n = 422,268) and upper respiratory tract infection (URI) (n = 744,942) were obtained from Georgia hospitals during 2002–2008. Spatially-contiguous daily concentrations of 11 ambient air pollutants were estimated from CMAQ model simulations that were fused with ground-based measurements. Using a case-crossover study design, odds ratios for 3-day moving average air pollutant concentrations were estimated using conditional logistic regression, matching on ZIP code, day-of-week, month, and year. RESULTS: In multipollutant models, the association of highest magnitude observed for the asthma/wheeze outcome was with “oxidant gases” (O(3), NO(2), and SO(2)); the joint effect estimate for an IQR increase of this mixture was OR: 1.068 (95% CI: 1.040, 1.097). The group of “secondary pollutants” (O(3) and the PM(2.5) components SO(4) (2−), NO(3−), and NH(4+)) was strongly associated with bronchitis (OR: 1.090, 95% CI: 1.050, 1.132), pneumonia (OR: 1.085, 95% CI: 1.047, 1.125), and otitis media (OR: 1.059, 95% CI: 1.042, 1.077). ED visits for URI were strongly associated with “oxidant gases,” “secondary pollutants,” and the “criteria pollutants” (O(3), NO(2), CO, SO(2), and PM(2.5)). CONCLUSIONS: Short-term exposures to air pollution mixtures were associated with ED visits for several different pediatric respiratory diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12940-016-0196-y) contains supplementary material, which is available to authorized users.